2011
DOI: 10.1111/j.1744-9987.2011.00908.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of β2‐Microglobulin in the Serum of Healthy Subjects Older Than 40 Years

Abstract: The aim of this research was to determine if the age of healthy subjects older than 40 years of age has an influence on the concentration of β(2) -microglobulin in the serum of subjects of different populations. We examined the values of β(2) -microglobulin in the serum of 51 healthy subjects aged 40-86 years using the microparticle enzyme immunoassay AxSYM β(2) -microglobulin test. The reference values of β(2) -microglobulin according to the nonparametric statistical method is 0.95-2.73 mg/L. A correlation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…For instance, one study has reported that healthy adults with an average age of 40 to 86 years old exhibit elevated serum B2M levels with progressive aging. Similar findings have been reported in other studies (20)(21)(22)(23). Additionally, B2M in the older Chinese population can reportedly affect both the frailty phenotype and index.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, one study has reported that healthy adults with an average age of 40 to 86 years old exhibit elevated serum B2M levels with progressive aging. Similar findings have been reported in other studies (20)(21)(22)(23). Additionally, B2M in the older Chinese population can reportedly affect both the frailty phenotype and index.…”
Section: Discussionsupporting
confidence: 91%
“… 18 As a polypeptide existed on the surface of most cells with a nucleus, B2MG is filtered by glomerular filtration and resorbed and decomposed in the proximal tubules. 19 However, KIM-1 was uncorrelated to serum CREA. CREA is a common biomarker that is filtered by the glomerulus but is not absorbed by proximal tubules.…”
Section: Discussionmentioning
confidence: 97%